Peranan Penanaman Modal Asing dalam Perekonomian: Penelitian - Khairani Alawiyah Matondang; Raymon Pernando Pasaribu; Selpiana; Feny Amelia Sinaga (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Foreign Direct Investment (FDI) plays a crucial role in driving Indonesia's economic growth, as regulated by Law Number 25 of 2007 concerning Investment. This study examines how FDI contributes to economic development, including increasing employment opportunities, transferring advanced technology, boosting foreign exchange earnings, and improving infrastructure facilities. Based on a review of various scholarly sources, it is evident that FDI has a significant positive impact on economic growth, although challenges remain, such as complex regulations and disparities in infrastructure development. The findings indicate that FDI is a key factor in promoting sustainable development and enhancing public welfare, and it is recommended to strengthen legal protection for foreign investors.